The lamb's high feast : Melito, Peri Pascha, and the Quartodeciman paschal liturgy at Sardis - Stewart-Sykes, Alistair. (Vigiliae Christianae, Supplements, 1998)
The purpose of this work is to determine the place of Melito's Peri Pascha in the paschal liturgy of the Quartodecimans at Sardis. Its conclusion is that Peri Pascha constitutes the two parts of the Quartodeciman liturgy. The first part of the work is a liturgical homily on Exodus 12 which was delivered on the eve of Pascha, and the second half is the text of a commemorative ritual which constituted the celebration of Pascha itself. This conclusion is based on a formal examination of the text in the contexts of Graeco-Roman rhetoric and of Jewish and Christian paschal liturgy and theology. This is the first full-length study of Peri Pascha to be published, and the first extensive study of the Quartodecimans since 1953.